2009
DOI: 10.1021/ja9043328
|View full text |Cite
|
Sign up to set email alerts
|

Shape-Selective Enantioselective Hydrogenation on Pt Nanoparticles

Abstract: The structure sensitivity of enantioselective hydrogenations on chirally modified metals was investigated using Pt nanoparticles of different shapes. All three samples had an average particle size of 10 nm, but the fraction of dominantly cubic, cubooctahedral, and octahedral particles varied with decreasing {100} and increasing {111} faces in the same order. In the absence of chiral modifier the hydrogenation of ethyl pyruvate was independent of the shape of the Pt nanoparticles; variation of the specific reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
144
2
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(160 citation statements)
references
References 93 publications
7
144
2
4
Order By: Relevance
“…Furthermore, it has been shown that the rate of hydrogenation and enantioselectivity outcome depends on the shape and terrace sites (Pt{100}or {111}) of the nanoparticles. Both the rate and the ee increased in the hydrogenation of ethyl pyruvate and ketopantolactone when Pt {111}nanoparticles were modified using CD or QN as the chiral modifiers (Schmidt et al, 2009). …”
Section: "Self-supported" and Solid-supported Heterogeneous Catalystsmentioning
confidence: 99%
“…Furthermore, it has been shown that the rate of hydrogenation and enantioselectivity outcome depends on the shape and terrace sites (Pt{100}or {111}) of the nanoparticles. Both the rate and the ee increased in the hydrogenation of ethyl pyruvate and ketopantolactone when Pt {111}nanoparticles were modified using CD or QN as the chiral modifiers (Schmidt et al, 2009). …”
Section: "Self-supported" and Solid-supported Heterogeneous Catalystsmentioning
confidence: 99%
“…The enantioselective catalysis on surfaces is commonly explained by three main mechanisms: the presence of chiral crystalline atomic structures at the surface, chiral adsorbates which modify the surface and chiral modifiers which control the approach of the substrate on the surface [11,12]. The stereoselective reactions mainly concern hydrogenations and C-C bond formation reactions based on the third mechanism [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. In this context, the optically pure ligand should be able to generate both a strong enough coordination at the metallic surface to stabilize MNPs and an asymmetric environment to efficiently lead to one of the expected stereoisomers during the organic transformation.…”
Section: Introductionmentioning
confidence: 99%
“…Ligands coordinate at the metallic surface by different ways, such as dative donor bonds between heteroatoms of the ligands and the metal surface, and also by π-interactions through aromatic fragments of the ligands and the nanoparticle. The nature of the chiral stabilisers reported in the synthesis of MNPs is wide-ranging, including dienes [15], cinchona alkaloids [16][17][18], mono or bidentate amines [19][20][21], phosphorus-based ligands (phosphites [22][23][24][25][26], diphosphines [27][28][29][30], secondary phosphine oxide [31]). P-stereogenic phosphines are well-known in catalysis using organometallic complexes as catalytic precursors, finding applications in hydrogenation, transfer hydrogenation, cyclopropanation, hydrovinylation, Diels Alder reactions and allylic substitutions [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Pt acts as catalyst in hydrogenations [2], in the reduction of polluting gases expelled during the combustion of gasoline in automobiles [3], in the industrial synthesis of nitric acid (from decomposition of petroleum) [4] and in proton-exchange fuel cell [5]. All of these applications use Pt finely divided [6].…”
Section: Introductionmentioning
confidence: 99%